Interdisciplinary Feeding Team: A Medical, Motor, Behavioral Approach to Complex Pediatric Feeding Problems. Issue 4 (July 2016) - McComish, Cara; Brackett, Kristen; Kelly, Maureen; Hall, Christine; Wallace, Sharon; Powell, Victoria
Abstract : Abstract: Pediatric feeding difficulties are complex and multifactorial in nature. Children who need assessment and individualized treatment for complex feeding problems are best served by an interdisciplinary treatment team. The medical, motor, and behavioral approach to treating pediatric feeding problems is presented as an avenue to treatment. By necessity, this approach requires a well-functioning interdisciplinary team, including nurses, physicians, registered dietitians, and feeding therapists (speech-language pathologists, occupational and physical therapists). We describe a robust interdisciplinary feeding team that applies a medical, motor, and behavioral approach to treating pediatric feeding problems. Within this team, pediatric gastroenterology nurse practitioners, dietitians, and speech pathologists function as integral members of the team. Description of each team member's expertise is provided and how they operate to support children with feeding problems and their families. Abstract : A team approach is ideal in working with children with feeding problems and their families. Members of many disciplines can contribute to successful outcomes when children are diagnosed with feeding problems. Nurses are key members of the interdisciplinary feeding team.